The foreign policy of China towards Afghanistan / Noor Ahmad Sahar and Raihanullah Rahimi - Sahar, Noor Ahmad; Rahimi, Raihanullah (UiTM Cawangan Johor, 2019)
Foreign Policy is the use of political influence in order to induce other states to exercise their law-making power in a manner desired by the states concerned: it is an interaction between forces originating outside the country's borders and those working within them. The policy pursued by People's Republic of China in order to achieve its national/international interests by maintaining relations with other states at international level is regarded as Chinese Foreign policy. The diplomatic relationship between Afghanistan and China started in 1955 when the first diplomat of Afghanistan, Abdul Samad, was posted to Peking. Historically, the two neighbouring countries were involved in trade relations with one another via Xin Jiang and Wakhan Corridor. This paper covers the role of China in the peace building and reconstruction of Afghanistan since 2001 as well as the foreign policy of China towards Afghanistan in the era of Xi Jinping and onwards as the complete paradigm shift of Chinese foreign policy in his era. In this paper, the foreign policy of China towards Afghanistan in different dimensions i.e.; trade, politics, defence etc. will be analysed. The discussion will revolve around the contemporary socio-economic, political and strategic relations between these states.